Analysis of Factors Affecting Compliance with Hotel Taxpayer Responsibility During the Covid-19 Pandemic (Case Study on Hotel X) - Apri Yani Melda; Mohamad Luhur Hambali (ITB AAS INDONESIA, 2023)
The Covid-19 pandemic has had a significant impact on the Indonesian economy as well as on the revenues of each region, especially of DKI Jakarta. The largest regional revenue sector for DKI Jakarta includes Regional Taxes which consist of various types, one of which is Hotel Tax. This thesis aims to analyze the factors that affect compliance with hotel tax obligations, to analyze the form of fulfillment of tax obligations as a form of compliance by Hotel Taxpayer X, and analyze Compliance Costs in fulfilling hotel tax obligations for hotel taxpayers during the Covid-19 pandemic (Case Study on Hotel X in 2020 and 2021). This research uses a qualitative approach by conducting literature studies and field studies through in-depth interview. Based on the research, it was found that the factors contributing to the compliance of Hotel Taxpayer X in carrying out their hotel tax obligations include the existence of sanctions, the fulfillment of hotel tax obligations which tend to be easy and cheap, and the risk of being examined by the tax authorities. Tax compliance at Hotel X is carried out by carrying out the obligations of registering, calculating, paying, and reporting hotel taxes owed. Suggestions that can be given include that Hotel X Taxpayers have more in-depth knowledge related to the allocation of tax funds, Hotel X Taxpayers can be more pro-active, and services, especially those related to tax administration carried out by the tax authorities, need to be re-optimized, evaluated, to provide easy, cheap, and fast services for Hotel Taxpayers.